The National Monetary Council as Monetary Authority:: Monetary Governance in the Period 1964-1994 - Franco, Gustavo H. B. (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2015)
With particular attention to the evolution of ideas concerning the composition of the National Monetary Council (CMN), according to different philosophies regarding the monetary institutions that they were intending to create, and discussing the modifications of the CMN and its meaning to the monetary governance in the country, in this article the author presents a survey of the evolution of the regulatory agencies of monetary policy in Brazil from the time of SUMOC (Superintendence of Money and Credit) (1945-1965), emphasizing the history of the Central Bank and of CMN.